A Nonhematopoietic Erythropoietin Analogue, ARA 290, Inhibits Macrophage Activation and Prevents Damage to Transplanted Islets. Issue 3 (March 2016) - Watanabe, Masaaki; Lundgren, Torbjörn; Saito, Yu; Cerami, Anthony; Brines, Michael; Östenson, Claes-Göran; Kumagai-Braesch, Makiko
Abstract : Background: Erythropoietin exerts anti-inflammatory, antiapoptotic, and cytoprotective effects in addition to its hematopoietic action. A nonhematopoietic erythropoietin analogue, ARA 290, has similar properties. The efficacy of pancreatic islet transplantation (PITx) is reduced due to islet damage that occurs during isolation and from the severe inflammatory reactions caused by the transplantation procedure. We investigated whether ARA 290 protects islets and ameliorates inflammatory responses following PITx thus improving engraftment. Methods: The effects of ARA 290 on pancreatic islets of C57BL/6J (H-2 b ) mice and on murine macrophages were investigated using an in vitro culture model. As a marginal PITx, 185 islets were transplanted into the liver of streptozotocin-induced diabetic mice (H-2 b ) via the portal vein. Recipients were given ARA 290 (120 μg/kg) intraperitoneally just before and at 0, 6, and 24 hours after PITx. Liver samples were obtained at 12 hours after PITx, and expression levels of proinflammatory cytokines were assessed. Results: ARA 290 protected islets from cytokine-induced damage and apoptosis. Secretion of pro-inflammatory cytokines (IL-6, IL-12, and TNF-α) from macrophages was significantly inhibited by ARA 290. After the marginal PITx, ARA 290 treatment significantly improved the blood glucose levels when compared to those of control animals ( P < 0.001). Upregulation of monocyte chemoattractant protein-1, macrophage inflammatory protein-1β, IL-1β, and IL-6 messenger RNA expression within the liver was suppressed by ARA 290 treatment. Conclusions: ARA 290 protected pancreatic islets from cytokine-induced damage and apoptosis and ameliorated the inflammatory response after PITx. ARA 290 appears to be a promising candidate for improvement of PITx. Abstract : Erythropoietin exerts anti-inflammatory, anti-apoptotic, and cyto-protective effects in addition to its hematopoietic action. Watanabe et al report that a nonhematopoietic erythropoietin analogue, ARA 290, protects islets from cytokine-induced damage and apoptosis by inhibiting IL-6, IL-12, and TNF-α secretion from macrophages.